High-resolution melting analysis for rapid and sensitive MYD88 screening in chronic lymphocytic leukemia - Jiang, Min (Oncol Lett, 2019)
High resolution melting (HRM) assay is a novel technology for the fast, high-throughput, sensitive, post-PCR analysis of genetic mutations. Myeloid differentiation primary response 88 (MYD88) mutations are frequently reported in chronic lymphocytic leukemia (CLL) and confer a worse prognosis. The objective of the present study was to assess the value of HRM analysis for the rapid screening of MYD88 mutations in patients with CLL. Genomic DNA samples were extracted from the bone marrow of 129 newly diagnosed patients with CLL. A plasmid with an MYD88-L265P mutation was constructed, and the p.L265P substitution, which is the predominant MYD88 mutation in CLL, was detected using HRM analysis and direct sequencing. The plasmid pCMV-MYD88-L265P-Mu was successfully constructed as a positive control, and was verified by direct sequencing. The normalized and shifted melting curves of 6/129 (4.65%) samples were clearly different from those of other patients by HRM analysis. In addition, the 794T>C mutation in MYD88 was identified in 6 (4.65%) patients by direct sequencing. Sensitivity evaluation revealed that the HRM assay had a higher sensitivity (to 1% dilution) than direct sequencing, in addition to being convenient and time-saving. The MYD88 p.L256P mutation has been implicated to be associated with adverse prognosis in CLL. HRM analysis has the potential to be a routine prescreening technique to identify the MYD88 p.L256P mutation and may facilitate the clinical treatment of CLL.